If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 = -1x + 15 Reorder the terms: -6 + 2x = -1x + 15 Reorder the terms: -6 + 2x = 15 + -1x Solving -6 + 2x = 15 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -6 + 2x + x = 15 + -1x + x Combine like terms: 2x + x = 3x -6 + 3x = 15 + -1x + x Combine like terms: -1x + x = 0 -6 + 3x = 15 + 0 -6 + 3x = 15 Add '6' to each side of the equation. -6 + 6 + 3x = 15 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = 15 + 6 3x = 15 + 6 Combine like terms: 15 + 6 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 3x+9x+10=13 | | 5u(2u+3)-2u(u-7)= | | 2x+127=12x-13 | | 3c^2-3c=4c | | 9-7x=84-42x | | 2x-5x=10 | | 5x^2-55x+20=0 | | 10-7x=103-28x | | x^2-16=-13 | | 112-7x=38+17 | | 140-3x=33x+20 | | 25x^2+11=15 | | 3x^2+18x-25=0 | | x^2-7x=7 | | 74+4x=9x+22 | | -119-7x=84-42x | | (x-5)*(x+8)= | | x^2+12x-5=0 | | x^2+(4-3)=26 | | x^2+4-3=5 | | x+5=105 | | -2=-4+3x | | w=f(a+r) | | 4x^2-7x+11=5x+6 | | 27-8(2-Y)=-13 | | 137-7x=29x+17 | | 27-8(2-7)=-13 | | 10x-2=38 | | 6x^2+37+35=0 | | 5y-4=2y+8 | | 14-10x=164-45x | | (x+7)*(x+2)= |